2009
DOI: 10.1177/0009922809343720
|View full text |Cite
|
Sign up to set email alerts
|

Hematemesis and Pyloric Stenosis

Abstract: An 11-week-old male infant was brought to an outside emergency department (ED) with the chief complaint of coffee ground emesis. He was vomiting about half of his feeds, 2 to 3 times a day for the last 2 days. On the day of presentation to the ED, he had 8 episodes of emesis over a 2-hour period, all of which were described by the mother as coffee ground and projectile. He usually drank 4 oz of Similac with iron every 2 to 3 hours, but his mother reported that it had decreased to 2 oz every 3 hours over the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In contrast, bilious emesis in infants with HPS has not been widely described. After an extensive literature search, we found multiple authors describing the vomit of IHPS as nonbilious, 7,10,11,16,17,19-24 but found only 1 case report, written in Hebrew, that suggests that bilious vomiting can be a presenting symptom. 26 Physiologically, bilious vomiting should not occur in a hypertrophied pylorus that prevents backflow of bile into the stomach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, bilious emesis in infants with HPS has not been widely described. After an extensive literature search, we found multiple authors describing the vomit of IHPS as nonbilious, 7,10,11,16,17,19-24 but found only 1 case report, written in Hebrew, that suggests that bilious vomiting can be a presenting symptom. 26 Physiologically, bilious vomiting should not occur in a hypertrophied pylorus that prevents backflow of bile into the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]17,18 The description of the vomit seen in IHPS is commonly described as never containing bile, and when bilious vomiting is present, IHPS can be excluded from the differential diagnosis of the vomiting infant. 7,10,11,16,17,[19][20][21][22][23][24] There are a few reports of hematemesis being associated with IHPS, but the frequency of hematemesis is low. 3,10,20 Although bilious emesis has been described in the context of concomitant gastrointestinal malrotation, 25 there is only 1 case report of bilious emesis being described in IHPS without additional gastrointestinal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Common causes of hematemesis during infancy include gastritis, esophagitis, stress ulcer, vascular malformation, and pyloric stenosis. 8 It is rare for congenital duodenal obstruction to present with acute gastrointestinal bleeding. 9 On review of the literature, there have been less than 10 cases of incomplete duodenal obstruction with hematemesis in early life reported in the English literature; even fewer cases of duodenal web with hematemesis.…”
Section: Discussionmentioning
confidence: 99%